Peningkatan Mutu Satuan Kelompok Bermain Melalui Pembimbingan Akreditasi - Muhammad Akil Musi; Azizah Amal; Muhammad Yusri Bachtiar; Fadhilah Afifah; A. Sri Wahyuni Asti (Universitas Negeri Makassar, 2024)
This accreditation guidance activity is carried out based on an analysis of the situation and problems found where the perception of educators and PAUD education staff is still low on the implementation of accreditation. This mentoring activity was carried out for one day at the An Nur Khaeriyah Playgroup located in Tanete Rilau District, Barru Regency.The methods used in this mentoring activity are counseling, discussion and, as well as practice and assignments. The participants involved in this activity are 1 manager and 3 educators. Based on the results and discussion, it can be concluded that participants can absorb the material well and can and understand all the material presented by the supervisor. The success of mentoring activities cannot be separated from the strong desire of educators and education staff as well as discipline during mentoring activities. The reflection of this mentoring activity was that the participants in general could absorb the material well, but there were still some things that needed to be improved, especially in the aspect of implementing the STPPA indicators